Process Optimization Study of Pb(II) Removal by Bulk Liquid Membrane (BLM) - H. Yousif, Nashwan; M. Flayeh, Hussain (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
Box-Wilson experimental design method was employed to optimized lead ions removal efficiency by bulk liquid membrane (BLM) method. The optimization procedure was primarily based on four impartial relevant parameters: pH of feed phase (4-6), pH of stripping phase (9-11), carrier concentration TBP (5-10) %, and initial metal concentration (60-120 ppm). maximum recovery efficiency of lead ions is 83.852% was virtually done following thirty one-of-a-kind experimental runs, as exact through 24-Central Composite Design (CCD). The best values for the aforementioned four parameters, corresponding to the most restoration efficiency were: 5, 10, 7.5% (v/v), and 90 mg/l, respectively. The obtained experimental data had been utilized to strengthen a semi-empirical model, based on a second-degree polynomial, to predict recovery efficiency. The model was tested using ANOVA software (Design expert®) and found acceptable R-Squared were (0.9673). Yield responseurface and contour plots have been created using the developed model, which revealed the presence of high-recovery plateaus whose specs will be useful in controlling pilot or industrial scale future devices to ensure economic feasibility.